Urban biodiversity from research to practice - Ossola, Alessandro; Niemela, Jari (London Routledge, Taylor & Francis Group, 2018)
Urban biodiversity is an increasingly popular topic among researchers. Worldwide, thousands of research projects are unravelling how urbanisation impacts the biodiversity of cities and towns, as well as its benefits for people and the environment through ecosystem services. Exciting scientific discoveries are made on a daily basis. However, researchers often lack time and opportunity to communicate these findings to the community and those in charge of managing, planning and designing for urban biodiversity. On the other hand, urban practitioners frequently ask researchers for more comprehensible information and actionable tools to guide their actions. This book is designed to fill this cultural and communicative gap by discussing a selection of topics related to urban biodiversity, as well as its benefits for people and the urban environment. It provides an interdisciplinary overview of scientifically grounded knowledge vital for current and future practitioners in charge of urban biodiversity management, its conservation and integration into urban planning. Topics covered include pests and invasive species, rewilding habitats, the contribution of a diverse urban agriculture to food production, implications for human well-being, and how to engage the public with urban conservation strategies. For the first time, world-leading researchers from five continents convene to offer a global interdisciplinary perspective on urban biodiversity narrated with a simple but rigorous language. This book synthesizes research at a level suitable for both students and professionals working in nature conservation and urban planning and management.--Provided by publisher.
1. Bringing Urban Biodiversity Research into Practice -- 2. Soil as a foundation to urban biodiversity -- 3. Urban biodiversity and ecosystem services -- 4. Planning for protection: Promoting pest suppressing urban landscapes through habitat management -- 5. Urban agriculture: an opportunity for biodiversity and food provision in urban landscapes -- 6. Urban biological invasions: when vertebrates come to town -- 7. Management of plant diversity in urban green spaces -- 8. Managing biodiversity through social values and preferences -- 9. Biodiversity and psychological well-being -- 10. Governance perspectives on urban biodiversity -- 11. Managing urban green spaces for biodiversity conservation: an African perspective -- 12. Urban green infrastructures and ecological networks for urban biodiversity conservation -- 13. Designing nature in cities to safeguard meaningful experiences of biodiversity in an urbanizing world -- 14. Biodiversity‐friendly designs in cities and towns: towards a global biodiversinesque style -- 15. Integrating urban biodiversity mapping, citizen science and technology
"Earthscan from Routledge"--Title page.
Includes bibliographical references and index.
Keywords: Urban ecology (Biology) -- Research